Cutaneous vasculitis: Lessons from COVID-19 and COVID-19 vaccination - Corrà, Alberto; Verdelli, Alice; Mariotti, Elena Biancamaria; Ruffo di Calabria, Valentina; Quintarelli, Lavinia; Aimo, Cristina; Sunderkötter, Cord H.; Caproni, Marzia (Frontiers in Medicine, 2022)
Cutaneous vasculitis are inflammatory skin-limited vascular disease affecting dermal and/or hypodermal vessel wall. From the pathogenetic point of view, idiopathic forms are described as well as the induction from various triggers, such as drugs, infections or vaccines. Following SARS-CoV-2 pandemic outbreak, cases of cutaneous vasculitis induced by both COVID-19 and COVID-19 vaccinations have been reported in literature. The aim of our work is collecting multiple cases available in literature, analyzing the frequency of the different forms of induced vasculitis, as well as their histological and immunopathological features. Although rare, cutaneous vasculitis induced by SARS-CoV-2 and vaccines may provide interesting insights in pathogenesis of these inflammatory processes which may in future be useful to understand the mechanisms underlying cutaneous and systemic vasculitis.